2003
DOI: 10.1212/01.wnl.0000042423.36650.bd
|View full text |Cite
|
Sign up to set email alerts
|

The pentapeptide QYNAD does not block voltage-gated sodium channels

Abstract: These experiments do not show any sodium channel blocking effect of QYNAD. The conclusion that QYNAD contributes to the pathophysiology of inflammatory neurologic disorders by blocking voltage-gated sodium channels should therefore be viewed with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Although endogenous TTXR Nav1.8 channels run down in culture (17, 28), by using the Nav1.8 shRNA-IRES-dsRED plasmid we further decreased Nav1.8 to minimize contamination. TTXR Nav1.9 currents are not observed under our recoding parameters as previously reported (7, 11). Endogenous TTXS channels were blocked with 500nM.…”
Section: Methodssupporting
confidence: 85%
“…Although endogenous TTXR Nav1.8 channels run down in culture (17, 28), by using the Nav1.8 shRNA-IRES-dsRED plasmid we further decreased Nav1.8 to minimize contamination. TTXR Nav1.9 currents are not observed under our recoding parameters as previously reported (7, 11). Endogenous TTXS channels were blocked with 500nM.…”
Section: Methodssupporting
confidence: 85%
“…While Cummins et al [6] conclude that the purported blocking action of QYNAD should be viewed with caution, our findings corroborate the earlier observations of Brinkmeier et al [3]. In our hands the QYNAD-related effects on voltage-gated sodium channels were observed upon sufficient equilibration of the peptide in the external bath solution, and by holding the membrane at hyperpolarized potentials for at least 3 min before the voltage protocols were applied after stabilization of the membrane seal.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that proper equilibration of the peptide in the bath was essential before we could proceed with the experimental protocols. In the recent report by Cummins et al [6] the voltage dependence of activation and steady-state inactivation were measured after exposure to QYNAD for 1.5-2 min. Our earlier attempts with the peptide without equilibration failed to show the changes in the voltage dependence characteristics or the frequencydependent block reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations